Epigenetic programming reshapes innate immune memory: decoding the molecular imprint of gouty inflammation - Su, Wenjie; Lu, Yifan; Luo, Zhiqiang; Xiong, Hui (Frontiers in Pharmacology, 2025)
Gout is an inflammatory joint disease caused by abnormal uric acid metabolism, characterized by the deposition of urate crystals in joints and surrounding tissues, leading to acute or chronic inflammatory responses. The etiology and pathogenesis of gout are complex, and there is currently a lack of ideal therapeutic drugs and treatment strategies. Epigenetic modifications influence and regulate gene function and characteristics through mechanisms such as DNA methylation, histone modifications, chromatin remodeling, and non-coding RNA, thereby exerting significant effects on the physiological and pathological states of the body. Recently, epigenetic modifications and trained immunity in gout have garnered increasing research interest. Epigenetic modification-mediated trained immunity represents a frontier area in the study of gout pathogenesis. This review summarizes the latest findings on the role and regulatory mechanisms of epigenetic modifications in the development of gout, as well as the role of epigenetic remodeling-mediated trained immunity in gout and the potential applications of epigenetic intervention strategies in gout, providing new insights into the relationship between persistent inflammation, epigenetics, and innate immune memory in gout.